2007
DOI: 10.1007/s15010-007-6356-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Nosocomial Infection with Extended-Spectrum Beta-Lactamase-Producing Bacteria in a Neonatal Intensive Care Unit in China

Abstract: Preterm low birth weight, prolonged mechanical ventilation and prior use of third-generation cephalosporins are risks factors for nosocomial infection with ESBL-producing bacteria in NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 32 publications
6
47
4
Order By: Relevance
“…Previous reports indicated conflicting findings in different settings. 25,26 Our understanding is that central venous catheter by itself is not a risk for ESBL, but the care and handling of central venous catheter is a key for the prevention of ESBL and for sepsis in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports indicated conflicting findings in different settings. 25,26 Our understanding is that central venous catheter by itself is not a risk for ESBL, but the care and handling of central venous catheter is a key for the prevention of ESBL and for sepsis in general.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Antibiotic restriction policy can significantly reduce antimicrobial consumption and antimicrobial resistance rates. 27 We have demonstrated that neonates with infections due to ESBL K. pneumoniae had a significantly higher mortality than those without ESBL K. pneumoniae infection.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] However, some of these associations were not observed in this study, and we further identified antibiotic exposure of third-generation cephalosporin and carbapenem within 1 month before GNB bacteremia as the independent risk factor. These diverse results can be explained by the different definitions of a resistant GNB isolate, [24][25][26][27] different study designs, 24,25 different empirical antibiotic policies, and different inclusion criteria (nosocomial infection instead of bacteremia in the other studies).…”
Section: Discussioncontrasting
confidence: 54%
“…[24][25][26][27] However, some of these associations were not observed in this study, and we further identified antibiotic exposure of third-generation cephalosporin and carbapenem within 1 month before GNB bacteremia as the independent risk factor. These diverse results can be explained by the different definitions of a resistant GNB isolate, [24][25][26][27] different study designs, 24,25 different empirical antibiotic policies, and different inclusion criteria (nosocomial infection instead of bacteremia in the other studies). 24,25,27 Previous antibiotic therapy has been recognized to be significantly related to bacterial resistance development, [24][25][26][27][28] but all issues regarding appropriate control group selection, case definition, description of previous antibiotic exposure, and adjustment for confounding factors should be refined.…”
Section: Discussioncontrasting
confidence: 54%
“…The presence of three or more of these predisposing factors (for children older than 30 days), has a sensitivity to detect patients with EPE ~84.6% and a specificity ~96.4%. RF for EPE infections in newborns involves different aspects, mostly related to the perinatal period [13].…”
Section: The Studymentioning
confidence: 99%